Konsep Penyelesaian Perselisihan Kontrak Kerja Antara Pekerja Dengan Perusahaan Melalui Serikat Pekerja Pada PT Intermoda Kusuma - Resya Dwi Marselina; Indri Fitriani; Leniawati Leniawati; Dede Restiani; Nur Anggraeni; Aulia Rahma Agysta (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In industrial relations, there will definitely be conflicts between companies and workers related to differences in ideas which result in industrial relations problems or known as industrial relations disputes. Based on this, if an industrial relations dispute occurs and the company or workers do not find a good decision then this dispute will be handed over to the labor union to be resolved so as to obtain a mutually beneficial solution between the two disputing parties. This research aims to find out how labor unions can be a solution to resolving industrial relations disputes that occur between companies and workers. In order to gain accurate information and avoid changing any data, this research adopts a descriptive analytic method, gathering data from journals and publications published by competent and qualified authors. The topic taken to conduct this research is the concept of resolving employment contract disputes through labor unions. The results of this research are the concept used by trade unions, namely through deliberation to reach consensus in a friendly and open manner so that disputes can be resolved peacefully and ensure that no party is harmed.